A Quantitative Study on Expenditure Behavior among Public and Private University Students in Malaysia - Sandrasegaran, Kavithanjali; Rambeli, Norimah (Journal of Economics and Behavioral Studies, 2023)
The principal point of this study is to examine the relationship between the spending pattern and consumer behavior, especially as it relates to income and financial literacy, among public and private university students in Malaysia. This study adopts Keynes’s Psychological Law of Consumption theory. The foremost objective of this theoretical paper was to determine whether there is any difference in spending patterns among public and private university students and the association between parental incomes and spending behavior among public and private university students, as well as to examine the relationship between financial literacy and spending behavior among public and private university students. In addition, this study seeks to determine how well students comprehend the idea of needs and desires. The association between students’ degree of financial literacy as well as their income and their spending habits will next be examined using the data. The link between endogenous and exogenous variables will be determined over both the long and short terms using the Statistical Package for the Social Sciences (SPSS) version 23. The study includes the findings from earlier investigations. The study contributed to a new understanding for the researcher of financial behavior under the categories of needs and wants which outline the importance of financial literacy, parents’ income, and demographic factors. The study also contributes to a new idea for policymakers: adapt financial literacy programs among parents and children.